Perbedaan Pengaruh Pembelajaran Berbasis Proyek dan Discovery Learning terhadap Kreativitas Siswa Kelas V Materi Perpindahan Kalor - Mashodi, Af'idatul Azkiyah; Maulana, Maulana; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2019)
Science concepts can be developed in everyday life because of their coverage of the environment and the environment of the surrounding community, so creativity is needed since students are at an early age. Creativity has been in students since he was born, in this case, the teacher is tasked with developing the creativity that is in students. Through the project-based learning model and discovery learning, students will be able to improve their creativity because learning is centered on students and students are free to express themselves. The purpose of this study was to determine the increase in creativity of class V students by implementing a project-based learning model and discovery learning, and to find out the differences between the two groups. The study used the quasi-experimental design and design of the nonequivalent control group design. The study population was all fifth-grade students in the North Sumedang Subdistrict, with a sample of study namely fifth-grade students of Sindang II Elementary School (project-based learning), and Sindang IV Elementary School (discovery learning). Based on the results of the study, the project-based learning model and discovery learning model can improve the creativity of class V students in heat transfer material, but the discovery learning model is significantly better in increasing the creativity of class V students in heat transfer material with a second test of gain average difference the group obtained sig (1-tailed) of 0.338.